Childfree: Between the Sacredness of Religion, Law and the Reality of Society - Nurjanah, Siti; Nur, Iffatin (Universitas Islam Negeri Raden Intan Lampung, 2022)
One of the fundamental problems of a cultural shift in the contemporary era today is the existence of a phenomenon that is contrary to the norm. One of them is the childfree phenomenon with the main goal being the voluntary choice not to have children in a family. Seeing this phenomenon, it seems that it has brought about a shift that must be answered from the perspective of religion, Islamic law, and the reality of society. This is because so far the position of children in religion, law, and the reality of society is a group that must be protected. With the above problems, this study aimed to formulate an approach to the childfree phenomenon from the point of view of Islamic law, particularly the objectives of Islamic law (maqāshid sharī'ah) and the reality of society. Through literature review and literature study, this study finds that the main dimensions of the Islamic law approach model based on maqashid shari'ah and the reality of society are based on the benefit to be addressed and are in line and tandem with the reality of society. The phenomenon of being childfree is contrary to the mission and objectives of maqāshid sharī'ah and the reality of society. The conclusion of this study has strengthened the discourse of an Islamic Law study on the childfree phenomenon as one of the contemporary phenomena that should be responded to by using the perspective of benefits to people. Salah satu problem mendasar dari pergeseran budaya di era kontemporer saat ini adalah adanya fenomena yang berseberangan dengan kelaziman. Salah satunya adalah adanya fenomena childfree dengan tujuan utamanya adalah peniadaan anak dalam sebuah keluarga. Melihat fenomena tersebut, nampaknya membawa arus pergeseran yang harus dijawab oleh kaca mata agama, hukum Islam, dan realitas masyarakat. Hal ini dikarenakan selama ini posisi anak dalam agama, hukum, dan realitas masyarakat merupakan kelompok yang harus dilindungi. Dengan problem di atas, kajian ini bertujuan untuk merumuskan pendekatan terhadap fenomena childfree dengan kaca mata hukum Islam, terkhusus tujuan hukum Islam (maqashid syari’ah) dan realitas masyarakat. Melalui kajian pustaka dan studi literatur, kajian ini menemukan bahwa dimensi utama model pendekatan hukum Islam berbasis maqashid syari’ah dan realitas masyarakat didasarkan oleh kemaslahatan yang hendak dituju dan sejalan serta beriringan dengan realitas masyarakat. Terhadap fenomena childfree, childfree bertentangan dengan misi dan tujuan maqashid syari’ah dan realitas masyarakat. Kesimpulan dalam kajian ini telah menguatkan diskursus kajian hukum Islam bahwa fenomena childfree merupakan satu dari fenomena kontemporer yang harus direspon dengan kaca mata kemaslahatan dalam masyarakat.